2017
DOI: 10.1002/eap.1621
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends in trait structure of riverine communities facing predation risk increase and trophic resource decline

Abstract: Many large European rivers have undergone multiple pressures that have strongly impaired ecosystem functioning at different spatial and temporal scales. Global warming and other environmental changes have favored the success of invasive species, deeply modifying the structure of aquatic communities in large rivers. Some exogenous species could alter trophic interactions within assemblages by increasing the predation risk for potential prey species (top-down effect) and limiting the dynamics of others via resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 95 publications
0
19
1
Order By: Relevance
“…Benthic macroinvertebrate abundance is similar in the two studied sites (Latli, Descy et al, 2017). The family richness is slightly higher at Waulsort (28) than at Ham-sur-Meuse (25) mainly due to exotic taxa that represent >80% of the sampled organisms.…”
Section: Study Areamentioning
confidence: 81%
See 4 more Smart Citations
“…Benthic macroinvertebrate abundance is similar in the two studied sites (Latli, Descy et al, 2017). The family richness is slightly higher at Waulsort (28) than at Ham-sur-Meuse (25) mainly due to exotic taxa that represent >80% of the sampled organisms.…”
Section: Study Areamentioning
confidence: 81%
“…In another study, we showed that plankton decline and increased predation risk (e.g. the great cormorant Phalacrocorax carbo and the European wels Silurus glanis ) influenced trophic structure of the fish community of the Meuse River (Latli, Descy et al., ), which could potentially differ according to the diet type and the importance of human perturbation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations